The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.jcm.2013.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A Collaborative Approach Between Chiropractic and Dentistry to Address Temporomandibular Dysfunction: A Case Report

Abstract: Objective: The purpose of this case report is to describe the chiropractic and dental comanagement of a patient with temporomandibular dysfunction, headaches, and myalgia. Clinical features: A 38-year-old black female patient presented for chiropractic care with a chief concern of jaw pain, tinnitus, headaches, and neck and shoulder soreness of 8 months' duration. The patient rated the pain a 6/10. The patient had a maximum mouth opening of 42 mm, graphed evidence of disk displacement, loss of translation on o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 20 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…Chiropractic therapy may also provide additional benefits to patients. Many studies found that chiropractic techniques, including Chiropractic BioPhysics (CBP) and activators, are highly effective in reducing stress and improving the quality of life in patients with TMD [24][25][26][27]. Chiropractors play a crucial role in the early diagnosis and treatment of TMD and can further prevent the development of chronic TMD and degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…Chiropractic therapy may also provide additional benefits to patients. Many studies found that chiropractic techniques, including Chiropractic BioPhysics (CBP) and activators, are highly effective in reducing stress and improving the quality of life in patients with TMD [24][25][26][27]. Chiropractors play a crucial role in the early diagnosis and treatment of TMD and can further prevent the development of chronic TMD and degeneration.…”
Section: Discussionmentioning
confidence: 99%
“…The other analyzed articles were clinical case studies involving participants of both sexes (30,31,32,33,34) . These studies reported the effects of the following treatments on TMDs: myofunctional therapy (30) , global postural re-education (31) , occlusal adjustment using an orthopedic apparatus combined with electrostimulation (32) , orthodontic treatment (33) , and chiropractic combined with traditional therapy (34) . In all studies, the treatments conferred some kind of benefit to the participant, and an improvement in the signs and symptoms of TMDs were noticed.…”
Section: Discussionmentioning
confidence: 99%
“…For example, there were differences in the number of channels used for recording the muscular response, the amplitude and frequency range of the calibration signal, and the positioning of electrodes on the facial muscles. In addition, even though the studies' main focus was improvement in the patients' quality of life, only two of the articles addressed this theme (31,34) , and only one (31) used a quality-of-life protocol (WHOQOL-BREF) to check the effects of the treatment adopted.…”
Section: Discussionmentioning
confidence: 99%
“…After filling out the Kinnie-Funt Chief Complaint Visual Index for Head, Neck and Facial Pain and TMJ dysfunction [35,36], we found that she ranked the following as her top three complaints: right sore throat without infection; "migraine"-type headache; tired, sore, neck muscles. The patient also noted additional complaints such as the following: inability to open the mouth smoothly and evenly; clicking, popping temporomandibular joints, pain in jaw muscles, balance problems ("vertigo"), ear pain without infection, upper and lower back pain.…”
Section: Case Reportmentioning
confidence: 99%